Revising the EFL curriculum through the lens of a multidimensional gender perspective - Piquer, Verónica Mariela (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
Gender inequality, discrimination and violence are major problems everywhere in the world. In Argentina, several laws have been passed to address these issues. In spite of all this legal framework, gender justice is still a pending goal to be achieved. At university level, the interdisciplinary and multidimensional postgraduate workshop “Transforming the course curriculum: Workshop to integrate a gender perspective in the university curriculum”, is an initiative to revise and transform the university curriculum from a gender perspective under three main dimensions: epistemic, political and ethical. In this account, I am sharing an experience of curriculum revision from the previously mentioned multidimensional gender perspective carried out in an English as a Foreign Language (EFL) course from Universidad Nacional de Río Cuarto, Córdoba, Argentina. I am also presenting some key concepts to understand gender inequality and exclusion and some interesting initiatives on gender inclusion in Argentina.